Hedyotis dinganensis, a new species of Rubiaceae from Hainan, China - Wang, Qinglong; Yuan, Langxing; Tang, Huan; Wang, Zhunian; Wang, Maoyuan; Yang, Qing (Phytotaxa, 2019)
Hedyotis dinganensis, a new species of the family Rubiaceae is described and illustrated from Hainan, China. It is most similar to H. yazhouensis and H. paridifolia, but can be easily distinguished from the latter by the inflorescence terminal or upper axillary congested-cymose, capitate, or fasciculate, the calyx 7–8 mm long, the corolla tube ca. 8 mm, the stipules triangular to broadly triangular ca.10 mm long, marginally entire to glandular-serrate, acuminate or with 8–10 narrowly triangular to linear lobes or bristles 1–7 mm long, the stigmas exserted ca. 1.2 mm. The new species is accessed as as ‘Critically Endangered’ (CR) according to IUCN categories and criteria.